1881 N.Y. Laws 103, tit. 12, § 412 - (:unkn) unknown (General Publisher, 1881)
Prohibited the concealed carrying of any kind of fire-arms, any sharp or dangerous weapon usually employed in attack or defense of the person. Violators guilty of a misdemeanor.
--
Keywords: CARRY - CONCEALED